Interplay of multi-brand products as competitive strategies for multinational companies - Govender, Myendhren (University of the Witwatersrand, Johannesburg, 2023)
The mining and construction business environment is dynamic with customers' needs for products continuously changing according to business environments, market conditions and applications. Multinational companies are losing customer share and market share by only offering premium products that are narrowly aligned with selected customer needs. These premium products are at high price levels with more features than required for customers’ applications. Competitors identify the gap and create product offerings similar to multinational companies’ products, albeit with basic features, and offer them at lower pricing to attract customers, thus gaining market share from multinational companies. Therefore, it is critical for multinational companies to offer products that are aligned with market conditions and customer needs. This business venture explores the interplay of multibrand products as a competitive strategy for multinational companies and how this will increase market share for the multinational mining and construction company, Epiroc whilst meeting customer needs. Epiroc is losing market share year after year by only offering premium products into the market. Competitors have identified this gap between customer needs and Epiroc’s premium products, thereby penetrating the gap, and targeting Epiroc’s medium and small-segment customers. Competitors add perceived value in the form of cost-effective products in these segments. Competitors hold more than 50% market share of Epiroc's medium and small segment customers, valued over BZAR 1’432. Through a multibrand strategy, Epiroc will gain a competitive advantage, as Epiroc will have the first mover advantage, offering multibrand products aligned to customers' needs. Epiroc can win back lost business and gain new business by targeting competitors' customers.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration (MBA) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Mining and construction business; Multinational companies; Premium products; Epiroc; UCTD; SDG-8: Decent work and economic growth